2016
DOI: 10.1111/issj.12125
|View full text |Cite
|
Sign up to set email alerts
|

Corruption scandals, scandal clusters and contemporary politics in New Zealand

Abstract: While New Zealand enjoys a widely held view that it symbolises the qualities of a corruption‐free democracy, over the past several years corruption scandals have increased markedly in number and intensity. It appears that corruption is becoming a part of the language of politics in New Zealand in a new way. This article explores this proposition with a particular focus on the incidence and character of corruption scandals during politically significant periods. It is an exploratory and admittedly impressionist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In Denmark, there were two scandals in 2018: the money-laundering scandal at the Estonian branch of the Danske Bank and the embezzlement scandal at the Ministry for Children and Social Affairs' administrative department ( The Local , 2019). A content analysis of two newspapers found 622 New Zealand corruption stories during 2000–2016 (Barrett and Zirker, 2016, p. 229).…”
Section: Lessons For Combating Corruption In Other Countriesmentioning
confidence: 99%
“…In Denmark, there were two scandals in 2018: the money-laundering scandal at the Estonian branch of the Danske Bank and the embezzlement scandal at the Ministry for Children and Social Affairs' administrative department ( The Local , 2019). A content analysis of two newspapers found 622 New Zealand corruption stories during 2000–2016 (Barrett and Zirker, 2016, p. 229).…”
Section: Lessons For Combating Corruption In Other Countriesmentioning
confidence: 99%
“…Second, corruption scandals can suddenly come out as a “cluster” in which political opposition and the mass media reveal the dirty side of the political arena. According to Barrett and Zirker (2016, p. 231):Corruption scandals tend to be centrally linked with extensive news media coverage. They also tend to shed a very different light on the political arena than do individual scandals in terms of their impact on the erosion of values, and on casting doubt upon the viability of institutions, while confirming in their repetition the reality of problems in moral, institutional, and political leadership.…”
Section: Dynamics Of Corruption Scandalsmentioning
confidence: 99%
“…Along with other, less wellknown instances of interest, such as the bestowing of honours, or the use of government agencies overseas to promote particular industries or ministers, there is a fertile field for study. Barrett and Zirker (2016) however, have shown that examining scandals in New Zealand and in particular how the response to them fits into themes, can have excellent illustrative use in studying corruption and patterns in them. While they were concerned with changes in incidence over time, taking frequency of scandal as an indicator of changes, the brief examination here is focused more on patterns of scandal type; that is, where and who is being influenced, as well as how they intersect with the law.…”
Section: Timeline Of Corruption and Influence Scandals In New Zealandmentioning
confidence: 99%